Some fixed point results for generalized modified Fα-contractions in modular metric spaces and its applications - Hami Gündoǧdu; Mahpeyker Öztürk; Ömer Faruk Gözükızıl (Miskolc Mathematical Notes)
This paper introduces new generalizations of modified FαF